Tęsknota za imperium w najnowszej fantastyce rosyjskiej - Polak, Andrzej (Studia Rossica Posnaniensia, 2019)
The article describes a group of texts that make up the so-called imperial fantasy genre. The author points out the sources of fascination with the imperial idea as well as discusses the scenarios created by the fantasists to regain the status of the empire by Russia. A separate aspect is the ability to read the imperial fantasy with the use of conceptual tools developed on the basis of the postcolonial theory. The influence of neo-Eurasian concepts on the reality created by the writers of the imperial fantasy is also discussed.